Mathematics of finance 1,224 Fully solved problems - Zima, Petr, 1941-; Brown, Robert L., 1949- (New York : McGraw-Hill, 2011)
1,224 fully solved problems. Coverage of practical applications using actual business and financial transactions. Review problems at the end of the book for additional study or self-testing.
Keywords: Business mathematics -- Problems, exercises, etc; Business mathematics